Use of droplet vitrification for the conservation of a Senegalese cassava cultivar - Ndiaye, Aliou; Panis, Bart (International Society for Horticultural Science, 2025)
Known for its starchy roots, cassava is one of the most important crops in the world. In West Africa, the total production continues to increase with 33.5% of the world production in 2018. Cassava is the second staple food and one of the main sources of energy in these areas. However, in some countries such as Senegal, cassava cultivation has not experienced real development; it is used as a root vegetable as staple food. Adding to this problem is the negative effect of certain diseases such as those caused by the cassava mosaïc viruses, especially on the cultivation of some sensitive local cultivars such as ‘Soya’ and ‘Combo’. To fight against the decline of the diversity of the local cassava cultivars and in order to develop a virus sanitation method (called cryotherapy), preliminary studies using droplet vitrification, were carried out. The results obtained after two months of culture of cryopreserved meristems were very promising; an average survival rate of 90.33% and an average regeneration rate of 62.86% was obtained.